Workers’ knowledge, attitude and performance of a waste recycling center in Tehran metropolis regarding health aspects during the spread of Covid-19 - Mohsen Ansari; Mahdi Farzadkia (سلامت و محیط, 2022)
Background and Objective: Today, the issue of health aspects in urban waste management, especially recycling, has received a lot of attention during Covid-19 around the world. Therefore, the purpose of this research is to investigate the knowledge, attitude, and performance of workers of one of the waste recycling centers in Tehran metropolis regarding health aspects during the spread of Covid-19. Materials and Methods: This was a descriptive-analytical cross-sectional study and the study population was all workers working in one of the recycling centers of Tehran Municipality. The data collection tool was a researcher-made questionnaire with validity and reliability in four sections: demographic, knowledge, attitude, and practice of workers toward Covid-19 and solid waste. Results: Findings of the study showed that the highest number of workers employed were in the age group of 20 to 40 years (60 percent). The level of knowledge was about 80 percent and the lack of awareness was 20 percent. The level of workers' positive attitude, negative attitude, and lack of attitude were 79.71, 14.56, and 5.72 percent, respectively. The level of positive practice among workers was about 67.43 percent and the negative practice was 32.57 percent. Conclusion: The results clarified that in order to succeed in waste management programs in recycling centers, municipal waste managers should pay more attention to educational aspects, especially through the focus on programs and their development and adaptation for different age groups, especially 20 to 40 years.